2019
DOI: 10.3390/a12070129
|View full text |Cite
|
Sign up to set email alerts
|

A Hyper Heuristic Algorithm to Solve the Low-Carbon Location Routing Problem

Abstract: This paper proposes a low-carbon location routing problem (LCLRP) model with simultaneous delivery and pick up, time windows, and heterogeneous fleets to reduce the logistics cost and carbon emissions and improve customer satisfaction. The correctness of the model is tested by a simple example of CPLEX (optimization software for mathematical programming). To solve this problem, a hyper-heuristic algorithm is designed based on a secondary exponential smoothing strategy and adaptive receiving mechanism. The algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The environmental issue of logistics received much attention from the LRP research community recently. The impact of logistics activities to the surrounding environment is addressed in several works either by the minimization of CO 2 emission incurred (e.g., Govindan et al, 2014;Tang et al, 2016;Chen et al, 2018;Leng et al, 2018;Rabbani et al, 2018a;Leng et al, 2019aLeng et al, , 2019bLu et al, 2019b) as shown in 9.05% articles, or the minimization of fuel consumption (Akararungruangkul and Kaewman, 2018;Dukkanci et al, 2019;Khalafi and Zarei, 2019;Zhang et al, 2019b) related to the transportation cost of the system. The environmental issue discussed is not only restricted to the emission impact but also the negative risk that may be incurred from the decisions within an LRP model.…”
Section: Objective Functionmentioning
confidence: 99%
“…The environmental issue of logistics received much attention from the LRP research community recently. The impact of logistics activities to the surrounding environment is addressed in several works either by the minimization of CO 2 emission incurred (e.g., Govindan et al, 2014;Tang et al, 2016;Chen et al, 2018;Leng et al, 2018;Rabbani et al, 2018a;Leng et al, 2019aLeng et al, , 2019bLu et al, 2019b) as shown in 9.05% articles, or the minimization of fuel consumption (Akararungruangkul and Kaewman, 2018;Dukkanci et al, 2019;Khalafi and Zarei, 2019;Zhang et al, 2019b) related to the transportation cost of the system. The environmental issue discussed is not only restricted to the emission impact but also the negative risk that may be incurred from the decisions within an LRP model.…”
Section: Objective Functionmentioning
confidence: 99%
“…worst, the reason is that the estimation of FCCE depends on plentiful parameters which may change over traveling time. For a comprehensive view of the models and factors, the reader is referred to the surveys [21] and papers [20,[28][29][30][31].…”
Section: Plos Onementioning
confidence: 99%
“…There are many selection strategies (SA) include the simple random (SR) sampling, choice function (CF), genetic algorithm (GA) [45], [46], Tabu Search (TS) [47], [48], and quantum evolutionary algorithm (QEA) [25] strategies. SA falls into two categories: deterministic acceptance, which accepts the resultant solution based on the fitness or special rules; and non-deterministic acceptance, which accepts the resultant solution based on a threshold or probability [49].…”
Section: Hypey Heuristic Algorithmmentioning
confidence: 99%